Beyond ideal speech situations: Adapting to communication asymmetries in health care. (January 2014) - Gillespie, Alex; Reader, Tom; Cornish, Flora; Campbell, Catherine
Inclusive, unconstrained and honest communication is widely advocated as beneficial and ethical. We critically explore this assumption by reflecting upon our research in acute care, informal care and public health. Using Habermas' ideals of dialogue to conceptualise ideal speech, we concur with observations that health care is often characterised by intractable exclusions and constraints. Rather than advocating implementing the ideals of dialogue, however, we examine how people adapt to these difficult and intransigent contexts. Non-ideal contexts, we find, sometimes call for non-ideal responses. Deception and furthering personal interests, and thus departing from the ideals of dialogue, can be adaptive responses.